If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x * 26 = 0 Reorder the terms for easier multiplication: 3 * 26x = 0 Multiply 3 * 26 78x = 0 Solving 78x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '78'. x = 0 Simplifying x = 0
| 6(x-1)+2=6x-2 | | -7y=-10-8y | | 0=-4.9t^2+.686t | | J+(-3)=4 | | 7j+4=5j | | -5x-15=-20 | | 9y=9+10y | | -12+8+5=36 | | 2x+34x^2-322=0 | | 3+(-7)=f-3 | | 3y+9-8y+6-6=-5y-12 | | -12+3x=-6 | | 9n=-117 | | 3x+9-8x+6-6=-5x-12 | | 3+(-7)=4 | | -0.9+z=0.075 | | 69=3u | | 0.06x+0.02(7-x)= | | 6p+4= | | 8-3=3x-2-8x | | 4+e=8+(-2) | | 3(5x+3)=6x-3+5x+3 | | 10b+50=30 | | 10x^2+13x+-9=0 | | -(x+5)=-1 | | 5h-12=4h+6 | | 3(-4+3)=2 | | 8x^4-42x^2=0 | | 2(1[3u-7]1)=16 | | 2,5x-21=14 | | -4.6y=9.2 | | (8x^4-42x^2-10x)-3=0 |